Effect of high glucose, Porphyromonas gingivalis lipopolysaccharide and advanced glycation end‐products on production of interleukin‐6/‐8 by gingival fibroblasts. (11th July 2016) - Chiu, H‐C.; Fu, M. M‐J.; Yang, T‐S.; Fu, E.; Chiang, C‐Y.; Tu, H‐P.; Chin, Y‐T.; Lin, F‐G.; Shih, K‐C.
Abstract : Background and Objective: It is known that chronic periodontal infection can magnify the cytokine responses in patients with diabetes. Hyperglycemia increases the proinflammatory status, including the levels of advanced glycation end‐products (AGEs), in patients with periodontitis. However, whether AGEs have additional effects on the production of those proinflammatory cytokines in diabetic patients with periodontitis is still unknown. To examine in vitro the effect of hyperglycemia and AGEs on the amounts of interleukin (IL)‐6 and IL‐8 produced in periodontally infected gingiva, human gingival fibroblasts (HGFs) were stimulated with glucose, AGE‐modified bovine serum albumin (AGE‐BSA) and Porphyromonas gingivalis LPS in the present study. Material and Methods: Primary culture of HGFs was incubated with various concentrations of AGE‐BSA (0, 50, 100 and 200 μg/mL) and LPS (0, 10, 100 or 1000 ng/mL) at two different glucose concentrations – normal glucose (5 mm ) and high glucose (25 mm ). The amounts of IL‐6 and IL‐8 produced by HGFs were evaluated using ELISA. Expression of the AGE receptor on HGFs was determined by flow cytometry. Results: High glucose stimulated a significant increase in the production of IL‐6 and IL‐8 by HGFs compared with normal glucose. This enhanced production of IL‐6 and IL‐8 could also be observed in the presence of LPS and/or AGE‐BSA. When both LPS and AGE‐BSA were present, especially at high concentrations (≥ 500 μg/mL of LPS and ≥ 25 μg/mL of AGE‐BSA), a synergistic effect on IL‐8 production was found in the high‐glucose condition. Conclusions: A synergistic effect of the production of IL‐8 could be induced in HGFs with the combination of high glucose, LPS and AGEs.